Physical and sports activity during the COVID-19 pandemic - Raiola, G.; di Domenico, F. (Journal of Physical Education and Sport, 2021)
The SARS-COVID 19 pandemic, which has hit the planet in recent times, in addition to changing daily life habits, also has negative repercussions on indoor exercise and sports, due to the social restrictions imposed by governments to address and contain the contagion. As a first response to this change in the social habits of practicing indoor physical activity in gyms, physical activity and sports professionals have developed innovative and original design ideas for outdoor training by proposing different physical disciplines for different classes of users. However, knowledge of the state of the art relating to the adaptations and opinions of physical activity and sports clients following the closure of indoor gyms is still poor. Considering that this knowledge differs from territory to territory by type of social and environmental context, the problem of the study is limited to the territory of interest and towards which the attention of indoor gym managers is directed. The chosen area is that of the municipality of Fisciano (province of Salerno) where the users of the Studio Zen gym are interested, which has about 100 customers. The aim of the study is to quantify the level of participation in outdoor training activities organized in compliance with the anti-COVID legislation, paying particular attention to the effects of constraints on physical and sports practice. The study was conducted using the Cluster Analysis methodology which, through the administration of a questionnaire drawn up with the Google Forms platform, collected data relating to the level of motor and sports practice before and after the closure of the indoor gyms. The data collected show that the outdoor training proposal in this study did not have a high level of participation for various reasons, both subjective and objective, which led the subjects to choose other training methods or decide not to perform any motor or sports activity.